Azide‐Terminated RAFT Polymers for Biological Applications. Issue 4 (18th November 2020) - Jiang, Ziwen; He, Huan; Liu, Hongxu; Thayumanavan, S.
Abstract: Reversible addition‐fragmentation chain‐transfer (RAFT) polymerization is a commonly used polymerization methodology to generate synthetic polymers. The products of RAFT polymerization, i.e., RAFT polymers, have been widely employed in several biologically relevant areas, including drug delivery, biomedical imaging, and tissue engineering. In this article, we summarize a synthetic methodology to display an azide group at the chain end of a RAFT polymer, thus presenting a reactive site on the polymer terminus. This platform enables a click reaction between azide‐terminated polymers and alkyne‐containing molecules, providing a broadly applicable scaffold for chemical and bioconjugation reactions on RAFT polymers. We also highlight applications of these azide‐terminated RAFT polymers in fluorophore labeling and for promoting organelle targeting capability. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of the azide derivatives of chain transfer agent and radical initiator Basic Protocol 2 : Installation of an azide group on the α‐end of RAFT polymers Alternate Protocol : Installation of an azide group on the ω‐end of RAFT polymers Basic Protocol 3 : Click reaction between azide‐terminated RAFT polymers and alkyne derivatives